Improving livelihoods and nutrition in sub-Saharan Africa through the promotion of indigenous and exotic fruit production in smallholders’ agroforestry systems: a review - Jamnadass, Ramni H.; Dawson, Ian K.; Franzel, Steven; Leakey, R.R.B.; Mithöfer, D.; Akinnifesi, F.K.; Tchoundjeu, Z. (2011)
The cultivation of indigenous and exotic fruits for sub-Saharan Africa’s domestic markets can bring increased revenues for smallholders and improve the diets of local consumers. There are, however, many bottlenecks which need to be addressed so that wider benefits from such activities are realised. Here, we describe key interventions being taken to address current constraints. For indigenous fruit trees, it is necessary to set priorities for which species to promote and to engage in participatory domestication for the improvement of yield, quality and germplasm delivery to farmers. For exotic fruits, ‘south-south’ transfer of advanced cultivars and the development of small-scale commercial suppliers of planting material are required to reinvigorate production. For both indigenous and exotic species, a focus on improving market value chains to bring greater benefits to producers is needed. We describe where further work is required to increase efficiency in the sector and to favour smallholder involvement.